Pesticidal plant extract effect against major lepidopteran insect pests and their natural enemies in rice Oryza sativa L - Seni, Atanu; Pal, Rini; Mohapatra, Sanjukta; Mandal, Dipankar; Bansude, Sushil Kumar; Seth, Pinki; Barla, Sarita; Sahu, Jubuli (Frontiers in Insect Science, 2025)
Extracts of plants have been used to manage various insect pests, but little information is available about how effective they are in reducing crop damage or how they affect crop yield and beneficial insects in rice. Extracts from Azadirachta indica leaves, Lantana camara leaves, Nerium oleander leaves, Aegle marmelos leaves, Allium sativum cloves, and Citrus limon fruits, known to have insecticidal properties, were compared with two checks, viz., Azadirachtin 1% EC and standard insecticide Acephate 95 SG, for their efficacy against yellow stem borer (YSB), Scirpophaga incertulas (Walk.), and rice leaf folder Cnaphalocrocis medinalis (Guenee) and natural enemies in cultivated rice in Sambalpur, Odisha, India. Untreated rice plants served as control. An adjuvant, Tween 20 at 1%, was added with all the botanical extracts except the commercial formulation. Plant damage, insect population numbers, and yield were monitored during two consecutive wet seasons from 2022 to 2023. Mean rice yield was significantly higher in the A. indica and Acephate 95 SG treatments, i.e., 4.68 t/ha and 4.66 t/ha, respectively, compared to the control (2.27 t/ha) and were significantly at par with each other. The L. camara and A. indica treatments were effective against both the major lepidopteran rice insect pests. The highest cost–benefit ratio of (1:4.65) was obtained from the Acephate treatment and was closely followed by the A. indica treatment (1:3.74). All the studied botanicals had less impact on natural enemies than synthetic chemicals. Among these botanicals, the maximum mean population of predators (like spiders and carabid beetles) and parasitoids (like Tetrastichus schoenobii, Telenomus dignus, and Trichogramma japonicum) were observed in the A. indica and A. marmelos treatments. Although all the studied botanicals were effective against both the major insect pests in rice, the A. indica, A. marmelos, A. sativum, and L. camara treatments showed the most promising against rice insect pests, so they may be incorporated into integrated pest management of rice.